Under-utilized crops - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1995)
Underutilized crops: Pulses and vegetables edited by J T Williams, 1993 ISBN 0 412 46610 4 Published by Chapman and Hall, 2-6 Boundary Row, London SE1 8HN, UK